2021
DOI: 10.1044/2021_aja-20-00211
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Stress in U.S. Audiologists

Abstract: Purpose The goal of this study was to explore interview data related to occupational stress in U.S. audiologists. This study is part of a larger project: The Lived Experience of the Audiologist, which seeks to develop a richer understanding of audiologists' lived experience via interview and survey research. Method Demographic and interview data related to occupational stress were examined from 28 virtual interviews of clinical audiologists in the Unite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Audiologists around the world report a lack of government funding for audiology services ( Goulios & Patuzzi, 2008 ). Previous research has also found time demands to be the highest stress factor for HHPs ( Emanuel, 2021 ; Severn et al, 2012 ), but some suggest these factors may affect more public sector clinicians than independent private clinicians ( Mott et al, 2004 ). The flexible resource management of the private sector is likely to impact the significant differences between private and public sector speech testing provision observed in this study and globally.…”
Section: Discussionmentioning
confidence: 99%
“…Audiologists around the world report a lack of government funding for audiology services ( Goulios & Patuzzi, 2008 ). Previous research has also found time demands to be the highest stress factor for HHPs ( Emanuel, 2021 ; Severn et al, 2012 ), but some suggest these factors may affect more public sector clinicians than independent private clinicians ( Mott et al, 2004 ). The flexible resource management of the private sector is likely to impact the significant differences between private and public sector speech testing provision observed in this study and globally.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent research has suggested occupational stress may not be a function of work setting as much as it is a function of personality, that is, an individual's reaction to stress in general. 29 This hypothesis is yet to be examined critically; however, it is possible that both stress and burnout are more closely connected with personality traits than they are to demographics such as work setting. In the current study, participants who were concerned about the impact of OTC hearing aids had a significantly higher stress rating than participants who were not concerned.…”
Section: Discussionmentioning
confidence: 99%
“…31 Second, the nature of audiologists' perceptions of the pandemic at the time of this survey was that the pandemic would cause short-term, temporary changes. 29…”
Section: Limitationsmentioning
confidence: 99%
“…Most audiologists working in the field today provide direct patient care in a healthcare setting (Janota 2018). For clinical audiologists, a significant source of workplace stress is interpersonal conflict with patients that they perceive as demanding (Emanuel 2021; Severn et al 2012). All healthcare workers providing direct patient care no doubt encounter people they perceive as unkind from time to time.…”
Section: Transphobia In Patientsmentioning
confidence: 99%
“…Though audiology has been reported as one of the less stressful occupations in the United States (“Audiologist Ranks in Least-Stressful Jobs List,” 2016; CareerCast 2019), audiologists can experience significant work-related stress and burn-out. Conflict with both patients and colleagues cause much of the stress that audiologists experience (Emanuel 2021; Severn et al 2012). Not all audiologists are affected equally, however.…”
Section: Introductionmentioning
confidence: 99%